Water promotes the sealing of nanoscale packing defects in folding proteins - Fernandez, Ariel (2014)
A net dipole moment is shown to arise from a non-Debye component of water polarization created by nanoscale packing defects on the protein surface. Accordingly, the protein electrostatic field exerts a torque on the induced dipole, locally impeding the nucleation of ice at the protein–water interface. We evaluate the solvent orientation steering (SOS) as the reversible work needed to align the induced dipoles with the Debye electrostatic field and computed the SOS for the variable interface of a folding protein. The minimization of the SOS is shown to drive protein folding as evidenced by the entrainment of the total free energy by the SOS energy along trajectories that approach a Debye limit state where no torque arises. This result suggests that the minimization of anomalous water polarization at the interface promotes the sealing of packing defects, thereby maintaining structural integrity and committing the protein chain to fold.